The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/app10207128
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bacterial Contamination of Air at the Museum of King John III’s Palace at Wilanow (Warsaw, Poland): Selection of an Optimal Growth Medium for Analyzing Airborne Bacteria Diversity

Abstract: There is no standardized protocol for the assessment of microbial air contamination in museums and other cultural heritage sites. Therefore, most museums conduct such assessments based on their own guidelines or good practices. Usually, microbial air contamination is assessed using only classical microbiology methods with the application of a single growth medium. Therefore, this medium should be carefully selected to limit any selective cultivation bias. Metabarcoding, i.e., a next-generation sequencing (NGS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Even though the R2A medium was formulated for water samples it has been widely used to cultivate soil microorganisms, as it promotes low-growing heterotrophic bacteria (Chaudhary et al, 2019). It has been demonstrated that this medium capture much more diversity compared to many other widely used ones (Blickfeldt, Brain Heart Infusion, Frazier, Trypticase Soy, Lysogeny Broth, Nutrient and Yeast Extract) and it use has been promoted for the metabolomic profiling of soil bacteria (Dziurzynski et al, 2020; de Raad et al, 2021). Therefore, we believe that this culture medium and conditions promoted a competitive advantage for Klebsiella and Brevibacillus , since both are generalists, versatile and adaptable (Bakelli et al, 2022; Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the R2A medium was formulated for water samples it has been widely used to cultivate soil microorganisms, as it promotes low-growing heterotrophic bacteria (Chaudhary et al, 2019). It has been demonstrated that this medium capture much more diversity compared to many other widely used ones (Blickfeldt, Brain Heart Infusion, Frazier, Trypticase Soy, Lysogeny Broth, Nutrient and Yeast Extract) and it use has been promoted for the metabolomic profiling of soil bacteria (Dziurzynski et al, 2020; de Raad et al, 2021). Therefore, we believe that this culture medium and conditions promoted a competitive advantage for Klebsiella and Brevibacillus , since both are generalists, versatile and adaptable (Bakelli et al, 2022; Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The main disadvantage of this approach is that the majority of microorganisms are not cultivable on classical media, which neglects the importance of viable but not culturable microorganisms [ 64 ]. Furthermore, while rich media are commonly used, they are not suitable for the overall biodiversity analyses [ 65 ]. Nevertheless, a cultivation approach can provide important data concerning microbial phenotypes, especially when prolonged incubation periods and low-substrate media are used for the increased recovery of environmental isolates [ 66 , 67 ].…”
Section: Inspection Of Methodologies Applied For Identification Anmentioning
confidence: 99%
“…The significance of biofilms on historic surfaces has been examined in recent conservation literature, taking into consideration both biodeterioration and bio-protection mechanisms ( Favero-Longo and Viles, 2020 ). The detection of bacterial species especially human diseases bacteria would be made possible by a combination of two types of media using meta-barcoding studies to examine the bacterial contamination of the museum’s air which helps to confirm the biochemical and eco-physiological functions of microorganisms in degradation ( Dziurzynski et al, 2020 ). New analysis insights into microorganisms and their metabolisms was applied for the protection of artworks and conservation in terms of cost, effectiveness, safety and environmental sustainability ( Favero-Longo and Viles, 2020 ).…”
Section: Introductionmentioning
confidence: 99%